Problem and research capacious creation of optimal technologies and modernization of already existing airborne cybernetic complexes of moving objects - Блохин, Л. Н. (Proceedings of National Aviation University (archive), 1999)
Considered and formulated are the most important research organization and research technical problems of the most advanced branches of state economy - creation of airborne competitive cybernetic complexes of moving objects. Drafted and considered are the ways of the main stages of their solutions